The Urban History of Dinanagar (1849-1947): The Rise and Governance of Dinanagar (1849-1947) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The small sleepy town : Dinanagar inthe district and tehsil of Gurdaspur (Punjab) is situated in 32º.8’ K and75º.28’E on the Amritsar Pathankot Branch of Northern Railway, 20 Kilometersfrom Pathankot. After the name of its founder Adina Beg, who is said to havefounded it in 1730 A.D., the town was originally named as Adinanager. Adina Begbuilt it up his residence and cantonment on the banks of Hasti or Shah Nahar,when he was in growing stage of his political carrier. He seems to haveexercised his government mainly from this town, when later on he was made theGovernor of Behrampur and subsequently placed in charge of Jullundur Doab byZakriya Khan, Subedar of Lahore.